Relación del canon petrolero y la inversión pública en la Región Loreto periodo 2016- 2021 - Chaname Moreyra, Felipe Josue (2023)
The complex link between public investment and the price of oil in the Loreto area between 2016 and 2021 is the topic of the current thesis. Effective oil sector resource management is emerging as a critical obstacle to promoting socioeconomic development in this huge Amazon region. The study examines relevant background materials, such as studies on municipal management, the relationship between project execution and investment cost, and the variability of regional resource allocation. The inclusion of recent research examining the various effects of oil rates in various areas provides a detailed picture of regional dynamics. The main objective of the research is to understand how the variable allocation of oil prices has influenced the execution of public investment projects and, consequently, regional growth. In addition to pointing out patterns and trends, this research aims to provide areas for resource management reform, encouraging fair and effective allocation to optimize the benefits of the oil business and support the sustainable growth of Loreto.